Efektifitas Pemberian Tablet Fe dan Jus Pisang Ambon Dengan Tablet Fe Terhadap Kadar Hemoglobin - Sofia Mawaddah; Martha Noorjanah (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2020)
Nutritional problems that often occur in adolescent girls are iron deficiency or anemia. Anemia is a lack of red blood cells. One way to prevent anemia is by consuming Ambon banana by juice. The aim of the study was to determine the effectiveness of giving Fe tablets and Ambon banana juice with Fe tablets on hemoglobin levels in female students at SMP16 Petuk Ketimpun, Palangka Raya.This research is a quantitative study with an analytic observational method using a Quasy Experiment study with a two group only pre-post test design. The population in this study were 50 students of SMP 16 Petuk Ketimpun Palangka Raya, namely 25 students in grade 1 and 25 students in grade 2 with a total sample of 30 female teenagers. The results of data analysis using Wilcoxon test obtained p value <0.05, namely p = 0.001 which can be concluded that there is an effect of Fe tablets on increasing hemoglobin levels, Meanwhile, in the Fe table group combined with Ambon banana juice the results obtained p <0.05, namely p = 0.000 which can be concluded that there is a significant effect between Fe tablets and Ambon banana juice in increasing hemoglobin levels of female students.